To Waste or Not to Waste: Questioning Potential Health Risks of Micro- and Nanoplastics with a Focus on Their Ingestion and Potential Carcinogenicity - Gruber, Elisabeth S; Stadlbauer, Vanessa; Pichler, Verena; Resch-Fauster, Katharina; Todorovic, Andrea; Meisel, Thomas C; Trawoeger, Sibylle; Hollóczki, Oldamur; Turner, Suzanne D; Wadsak, Wolfgang; Vethaak, A Dick; Kenner, Lukas (Exposure and health, 2023)
Micro- and nanoplastics (MNPs) are recognized as emerging contaminants, especially in food, with unknown health significance. MNPs passing through the gastrointestinal tract have been brought in context with disruption of the gut microbiome. Several molecular mechanisms have been described to facilitate tissue uptake of MNPs, which then are involved in local inflammatory and immune responses. Furthermore, MNPs can act as potential transporters ("vectors") of contaminants and as chemosensitizers for toxic substances ("Trojan Horse effect"). In this review, we summarize current multidisciplinary knowledge of ingested MNPs and their potential adverse health effects. We discuss new insights into analytical and molecular modeling tools to help us better understand the local deposition and uptake of MNPs that might drive carcinogenic signaling. We present bioethical insights to basically re-consider the "culture of consumerism." Finally, we map out prominent research questions in accordance with the Sustainable Development Goals of the United Nations.
Keywords: Nanoplastic; Human health; Carcinogenesis; Microplastic; Bioethics issue